Neuromotorable capacities of field football players: professionals vs. non-professionals - Silva, Erley da (2024)
Introduction: modern football is a sport of British origin, in Brazil it has become a passion experienced by different cultures, with the purpose of leisure, entertainment or sports performance. Objective: to analyze neuromotor skills between professional players (PP) and non-professional players (NPP) who practice field Football. Materials and methods: the sample consisted of 20 male players, distributed in 10 PP and 10 NPP. Volunteers should have experience in Football practice for at least three years, a minimum frequency of twice a week and age between 18 and 25 years. The tests used to evaluate the players were respectively: sit and reach test for flexibility; Illinois Agility Test for Agility; 20m run for speed; horizontal jump for explosive strength and Running Anaerobic Sprint Test (Rast Test) for anaerobic power. Results: in the characteristics of the players, there was a significant difference only in relation to the weekly frequency, being higher for the PP (p<0.001). In neuromotor abilities, the PP showed better performance in agility (p<0.001), speed (p=0.047), mean absolute power (p=0.011) and mean relative power (p=0.022). Discussion: it is believed that the performance of the PP was superior due to the higher weekly frequency of training. Conclusion: PP showed better performances in agility, speed and anaerobic power compared to JPP.